Encyclopaedia of Terrarium - Bruins, Eugene; Challacombe, Stephen ([Lisse, Netherlands] : Rebo, 1999)
Presents facts about reptiles, amphibians, spiders, and insects, including accommodation, breeding, required care, feeding, and other important information.
Includes index.
7-A.
Keywords: Reptiles -- Encyclopedias; Amphibians -- Encyclopedias; Insects -- Encyclopedias; Terrariums